Exploration of Intellectual Software Systems and Development of Conceptual Model - Mahmudova, Shafagat (Review of Computer Engineering Research, 2020)
This article explores the field of artificial intelligence and intellectual systems. The structure, types and classification of the intellectual system are studied. The intellectual system is a technical or software system that is capable of solving the problems which are specific and creative in a particular subject area, so that knowledge is stored in the memory of such systems. Intelligent System is a technical or software system that competently solves the problems that are relevant to a particular subject area and that knowledge is stored in such systems. Intelligent systems are studied by a team of researchers called "artificial intelligence". The article provides the differences between the ordinary system and the intellectual system. The system is intellectual when it not only changes the parameters of information access, but also changes its behavior itself depending on the system capability. Intelligent system in decision-making technologies is an intellectual information-computing system that solves the problems without human involvement. The classification of intellectual systems is analyzed in the article. A conceptual model for intelligent systems has been developed. The intellectual systems themselves may also have some gaps. In future, the development of new intelligence systems and improvement of existing ones will benefit the economy even more.